Instrumentos urbanísticos à luz dos planos diretores: Uma análise a partir de um circuito completo de intervenç\~ao - Vicente Correia Lima Neto; Cleandro Henrique Krause; Renato Nunes Balbim (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper discusses the use of urban policy instruments in Brazil, brought by the City Statute (CS) a federal law passed in 2001 ("Estatuto da Cidade" in Portuguese), as a tool of analysis of municipal master plans (MP). The main argument of this research is that the municipal urban policy would be consolidated by the presence of MP as specified in the CS. However, the mere presence of this plan within the municipality may not reflect its effectiveness. Therefore, how to evaluate the cities master plans if not by their presence? The premise established for this research is that the integrated and detailed prevision of urban policy instruments provided by the CS in the MPs would develop more real and useful MPs. Such integration could be analyzed from the construction, prevision and detailing of a circuit of intervention in the urban space, which would bring the urban instruments as a transformative tool of cities. And, at first, a more detailed MP, without the need for further regulations, could make itself promptly operational. The choice of which instruments to analyse corresponds to those which: i) are more present in Brazil's urban reform ideary; ii) have tacit knowledge; and iii) enable the integrated use of other instruments. [...]
Keywords: R51; R52; 330; urban planning instruments; urban management; urban network